Students' understanding of plant classification using the PLANTA-FUN card game media - Debora Kristiani Rahardjo; Wahyu Hari Kristiyanto; Sri Kasmiyati (JURNAL BIOEDUKATIKA, 2021)
UNO card game-based learning media have been developed with various modifications. Therefore, there is a need for studies that describe the role and meaning of the symbols used in UNO card media on students' understanding. The purpose of this study is to describe the profile of students' understanding who were stimulated by symbols of meaning in the PLANTA-FUN card game media on plant classification material. The PLANTA-FUN card game media is a modification of the UNO card game created by combining the colors and images of the key-living creatures. This research was conducted using Mixed Method Research (quantitative-qualitative). Pre-test and post-test to determine students' understanding of classifying the plants. In addition, interviews were also conducted to evaluate students' understanding of the meaning of the symbols. Based on the pre-test and post-test results, the t-value (8.612) > the t-table (2.101). So it can be seen that there was an increase in students' understanding after learning using the PLANTA-FUN card game media. Based on the interview, symbols of meaning in the form of images and colors on the PLANTA-FUN card game media can help stimulate students to remember and think. The key character images of plants used in this media can naturally visualize plants so that students can quickly identify the characteristics that appear in these plants. At the same time, the color symbols that represent groups of living things can quickly stimulate students in recalling groups of plants. Combining these two symbols of meaning can improve students' understanding of plant classification learning material.